2006
DOI: 10.2337/db06-0030
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Restores Metabolic Function in Cultured Cortical Neurons Subjected to Oxidative Stress

Abstract: We previously demonstrated that insulin has a neuroprotective role against oxidative stress, a deleterious condition associated with diabetes, ischemia, and age-related neurodegenerative diseases. In this study, we investigated the effect of insulin on neuronal glucose uptake and metabolism after oxidative stress in rat primary cortical neurons. On oxidative stress, insulin stimulates neuronal glucose uptake and subsequent metabolism into pyruvate, restoring intracellular ATP and phosphocreatine. Insulin also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 51 publications
(68 reference statements)
3
71
0
Order By: Relevance
“…Yet, increased EPO secretion during diabetic pregnancies may represent the body's attempt at endogenous protection against the complications of DM (Teramo et al, 2004). Similar to the potential protective role of insulin (Duarte et al, 2006), EPO administration has been shown both in diabetics as well as non-diabetics with severe, resistant congestive heart failure to decrease fatigue, increase left ventricular ejection fraction, and significantly decrease the number of hospitalization days . In vitro studies with vascular cells exposed to elevated glucose also have elucidated a strong cytoprotective effect of EPO.…”
Section: Epo and Cellular Metabolismmentioning
confidence: 91%
“…Yet, increased EPO secretion during diabetic pregnancies may represent the body's attempt at endogenous protection against the complications of DM (Teramo et al, 2004). Similar to the potential protective role of insulin (Duarte et al, 2006), EPO administration has been shown both in diabetics as well as non-diabetics with severe, resistant congestive heart failure to decrease fatigue, increase left ventricular ejection fraction, and significantly decrease the number of hospitalization days . In vitro studies with vascular cells exposed to elevated glucose also have elucidated a strong cytoprotective effect of EPO.…”
Section: Epo and Cellular Metabolismmentioning
confidence: 91%
“…Yet, increased EPO secretion during diabetic pregnancies may represent the body's attempt at endogenous protection against the complications of DM (Teramo, et al, 2004). Similar to the potential protective role of insulin (Duarte, et al, 2006), EPO administration has been shown both in diabetics as well as non-diabetics with severe, resistant congestive heart failure to decrease fatigue, increase left ventricular ejection fraction, and significantly decrease the number of hospitalization days .Cell culture studies with vascular cells exposed to elevated glucose also have elucidated a strong cytoprotective effect of EPO . Administration of EPO can significantly improve EC survival in a 1.0 ng/ml range .…”
mentioning
confidence: 99%
“…Yet, increased EPO secretion during diabetic pregnancies may represent the body's attempt at endogenous protection against the complications of DM [258]. Similar to the potential protective role of insulin [259], EPO administration has been shown both in diabetics as well as non-diabetics with severe, resistant congestive heart failure to decrease fatigue, increase left ventricular ejection fraction, and significantly decrease the number of hospitalization days [205]. In studies that examine the toxic effects of elevated glucose upon vascular cells, EPO is protective and prevents early apoptotic membrane PS exposure and late DNA degradation at concentrations that are clinically relevant [110] to cellular protection in patients with cardiac or renal disease [260,261].…”
Section: Erythropoietin a Cytokine And Growth Factormentioning
confidence: 99%